Analyzing “Sunny” California: A Study of the Role of Solar Energy Subsidies in the Golden State - Grace Mendes (Bellarmine Law Society Review, 2022)
With a reputation for mild climate and progressive politicians, it is not surprising that California is at the forefront of the push towards renewable energy, particularly solar energy. But is solar really the energy panacea public opinion makes it out to be? Taking California as an explanatory microcosm, this article delves into the state’s own history with energy legislation and the energy market, as well as the consequences to the public psyche when energy is mismanaged. The article then explores the logistics and statistics of California solar production, while raising questions about the efficacy, extent, and direction of state and federal involvement in the process. This article ultimately concludes that in order to continue progress in the sphere of renewable energy, the focus of the movement should shift away from increasing solar construction and focus instead on increased solar access and the development of high capacity solar storage.